The effects of hydroalcoholic extract of Nigella sativa seed on oxidative stress in hippocampus of STZ-induced diabetic rats - Abbasali Abbasnezhad; Parichehr Hayatdavoudi; Saeed Niazmand; Maryam Mahmoudabady (Mashhad University of Medical Sciences, 2015)
Objective: Oxidative stress plays an important role in the etiology of diabetic complications. Diabetes impairs hippocampus neurogenesis, synaptic plasticity, and learning. The aim of this study was to investigate the effects of hydroalcoholic extract of Nigella sativa seed on oxidative stress in STZ-induced diabetic rats' hippocampus. Materials and Methods: Diabetes induced by 60 mg/kg STZ, i.p, and the rats were divided into five experimental groups (n=8-10 in each group) including control (received 0.5 ml normal saline), untreated STZ-diabetic (received 0.5 ml normal saline), and treated rats received Nigella sativa extract (200 and 400 mg/kg) or metformin (300 mg/kg) by gavage for 42 days. Serum glucose concentration and body weight as well as hippocampus tissue malondialdehyde and thiollevels were determined by calorimetric assay. Results: Serum glucose level in the diabetic rats treated with 200 mg/kg Nigella sativaextract at the days 24 and 45 decreased in comparison to untreated diabetic group (p